Microfinance : a reader - Arun, Thankom (London ; New York, NY : Routledge, 2009)
This book covers microfinance and poverty reduction, microfinance, gender and social development, microinsurance and regulating and supervising microfinance institutions.
An introduction to microfinance -- Microfinancial services and poor people -- Microfinance and poverty reduction -- Microfinance, gender, and social development -- Microfinance: innovations in product delivery -- Microinsurance -- Regulating and supervising microfinance institutions -- Impact assessment of microfinance -- The future of microfinance.
Includes bibliographical references and index.
aug 02/05/13
Loans
Keywords: Microfinance